Sample learning modules for developing reading comprehension skills among vocational secondary students - Eguna, Elsa Catelo 1943- (1979)
This study was conducted to construct sample learning modules for developing reading comprehension skills among vocational secondary students who are reading at the Grade Five level. A sample population of 15 were selected from among the first year secondary students of the Mainit National Agricultural School, Mainit, Surigao del Norte. The modules were administered to the 15 subjects to determine the indices of difficulty and discrimination of the items in the lessons included in the modules. The four reading comprehension skills developed in this study were Noting Details, Getting the Main Idea, Inferring Meaning Through Context and Outlining.